Flow cytometry detection of CD138 expression continuum between monotypic B and plasma cells is associated with both high IgM peak levels and MYD88 mutation and contributes to diagnosis of Waldenström macroglobulinemia. Issue 1 (25th February 2021) - Gayet, Mylene; Leymarie, Vincent; Derouault, Paco; Guérin, Estelle; Vaidié, Julien; Pascal, Virginie; Boulin, Mélanie; Dmytruk, Nataliya; Chauzeix, Jasmine; Trimoreau, Franck; Gachard, Nathalie; Feuillard, Jean; et al.
Abstract: Background: Differential diagnosis of Waldenström macroglobulinemia (WM) with other indolent B‐cell malignancies is still a challenge. Here, we propose an original and simple analysis of routine flow cytometry (FCM) unraveling the characteristic ongoing plasma cell (PC) differentiation of WM tumor B‐cells. Methods: FCM analysis of both B‐cells and PC was performed on a series of 77 patients with IgM peak. MYD88 and CXCR4 mutations were studied using an allele‐specific PCR and by high throughput sequencing. Results: Twenty seven (35%), 46 (58%) and 4 (5%) patients were classified as WM, IgM monoclonal gammopathy of undetermined significance (MGUS) or other B‐NHL respectively. MYD88 mutation was found in 25/27 WM (93%) and in 29/46 MGUS (63%). Using FCM, monotypic B‐cells were found in 27/27 WM (100%) and 34/46 MGUS (74%). Monotypic CD138pos/CD38pos PCs were detected in 23/27 WM (85%) and 25/46 MGUS (54%). Highlighting the ongoing PC differentiation of WM tumor B‐cells by FCM, we evidenced a CD138 expression continuum between monotypic B‐cells and PCs. This pattern remained absent in control samples and was significantly associated with higher IgM peaks ( p = 6.10 −5 ) and MYD88 mutations ( p = 10 −3 ) in both WM and MGUS cases. Conclusions: FCM exploration of both B‐cells and PC led to identify a CD138 expression continuum as an objective marker of ongoing PC differentiation of WM tumor cells and was strongly associated with increased IgM peak levels and MYD88 mutations. This approach could contribute to place FCM at the forefront of WM diagnosis.